Convention on biological diversity (1992) (Envirnomental Law and Institutions Programme Activity Centre NairobiKE, 1992)
Includes the Nairobi Final Act of the Conference for the Adoption of the agreed text of the Convention on Biological Diversity; resolutions and declarations; and the Convention on Biological Diversity.
DC